THE IMPACT OF PARTIAL REVERSAL OF PAYROLL EXEMPTION - Vasconcelos, Pedro Gomes (2019)
In 2015, with the worsening of Brazilian fiscal crisis, Law No. 13.161 was enacted,which reversed in part the exemption of payroll taxes, increasing and creating new ratesfor the social security contribution on gross revenue. Estimates suggest that there was areduction of R$ 5.4 billion in tax breaks involved. This article studied the impact of thisreversal, even partially, in the payroll tax exemption. A neoclassical model of generalequilibrium with closed economy and two intermediate firms was built to study thisimpact. The results suggest that the macroeconomic effects will be negative, but small. Inthe sectorial analysis, the firms that were originally benefited by payroll tax exemption maypresent losses of up to 1% in output, capital and working hours. On the other hand, forother firms, the reversal is positive, with small increases in output and employment in thesesectors.